Hubungan Pengetahuan Dan Sikap Ibu Hamil Dengan Kepatuhan Minum Tablet Tambah Darah - Mona, Silvia; Maharawati, Maharawati (Sehat MasadaJurnal, 2021)
Anemia turns into a widespread public health problem associated with an increased risk of morbidity and mortality particularly in pregnant women. Based on data from the District of Karimun Health Office in 2018, there was 74.54% expectant mothers got Fe 3 supplements in Karimun recorded in 2017, with mainly 88.52% in Meral and 54.37% in Tebing that was noted to be the lowest number. This research is an analytical survey research with cross sectional study design. The univariate analysis result indicates 69.0% respondents possess poor level of knowledge of the benefit of Fe 3 tablet for pregnant mother, besides, 67.9% of them show negative attitudes and 64.3% have no compliance in taking Fe supplement routinely. Furthermore, bivariate analysis shows a correlation between the knowledge levels of respondents and their agreement in having iron booster tablets with p value of 0.000 (<0.05). On the other hand, it is also confirmed a correlation between the attitudes of respondents and their compliance in consuming iron booster supplements with p value of 0.000 (<0.05). As suggestion, it is hoped all parties, especially the Puskesmas as the public health center, to be able to provide and assist the pregnant mothers about information of the advantages of Fe supplements for both the pregnant mother and the baby.